Perancangan Jam Kerja berdasarkan Beban Kerja Full Time Equivalent dan NASA–TLX pada Stasiun Kerja Printing PT. XYZ - Putra Asyifa Nurriza; Nur Rahman As’ad; Eri Achiraeniwati (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. PT. XYZ is a manufacturing company engaged in making food product packaging and beverage labels. Based on the results of observations, product defect problems were found at 15% at printing work stations. These defects were caused by color combination work and errors in the finished product inspection process carried out by the operator. This condition is caused by long working hours, namely 12 hours, the work demands precision and concentration in the color combination simulation process and manual inspection of finished products. This job requires physical ability and mental ability so that it can increase the risk of musculoskeletal injuries, increase mental and emotional stress, cause muscle tension and posture disorders. The aim of this research is to design working hours that are adjusted to the workload received by workers to ensure occupational safety and health. The method used to identify mental load is NASA -TLX and Full Time Equivalent (FTE) to determine the amount of physical labor. Research was conducted on 2 operators and 4 helpers, the results showed that the mental workload classification for both operators and helpers was high, ranging from 50 - 79. Measuring workload using FTE showed the operator index value was 1.4 (overload), while the helper index value was below 1 (UnderloadI). The proposed improvement is carried out by designing working hours from 12 hours to 8 hours and from 2 shifts to 3 shifts with the transfer of one helper to shift 3. Based on the improvement, working hours become 8 hours with 3 shifts resulting in a normal physical load with an FTE index value of 1.13 for operators and 1.04 for helpers. Abstrak. PT. XYZ adalah perusahaan manufaktur yang bergerak dibidang pembuatan kemasan produk makanan dan label minuman. Berdasarkan hasil observasi ditemukan permasalahan kecacatan produk sebesar 15% pada stasiun kerja printing. Kecacatan tersebut diakibatkan oleh pekerjaan pengkombinasian warna dan kesalahan proses pemeriksaan produk jadi yang dilakukan oleh operator. Kondisi tersebut disebabkan oleh jam kerja yang panjang yaitu 12 jam, pekerjaan menuntut ketelitian dan konsentrasi dalam proses simulasi pengkombinasian warna dan pemeriksaan produk jadi secara manual. Pekerjaan ini memerlukan kemampuan fisik dan kemampuan mental sehingga dapat meningkatkan risiko cedera musculoskeletal, meningkatkan stres mental dan emosional, menyebabkan ketegangan otot dan gangguan postur. Tujuan penelitian ini adalah perancangan jam kerja yang disesuaikan dengan beban pekerjaan yang diterima oleh pekerja untuk menjamin keselamatan dan kesehatan kerja. Metode yang digunakan untuk mengidentifikasi beban mental adalah NASA -TLX dan Full Time Equivalent (FTE) untuk menentukan jumlah tenaga kerja secara fisik. Penelitian dilakukan terhadap 2 operator dan 4 helper, hasil menunjukkan klasifikasi beban kerja mental baik operator maupun helper tinggi berkisar antara 50 – 79. Pengukuran beban kerja dengan menggunakan FTE menunjukkan nilai index operator adalah 1,4 (overload), sedangkan nilai index helper dibawah 1 (UnderloadI). Usulan perbaikan dilakukan dengan merancang jam kerja dari 12 jam menjadi 8 jam serta dari 2 shift menjai 3 shift dengan pemindahan satu helper kedalam shift 3. Berdasarkan perbaikan jam kerja menjadi 8 jam dengan 3 shift menghasilkan beban fisik yang normal dengan nilai index FTE 1,13 untuk operator dan 1,04 untuk helper.